1997
DOI: 10.1021/ic961312z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Unexpected Associative Displacement of Adenosyl by Cyanide in Coenzyme B12

Abstract: The reaction of coenzyme B(12) (adenosylcobalamin) with cyanide has been reinvestigated in detail using spectroscopic and kinetic techniques. It has been shown that this reaction proceeds in one kinetically observable step, contradicting previous findings, with rate-determining attack of the first cyanide (k = (7.4 +/- 0.1) x 10(-3) M(-1) s(-1), 25.0 degrees C, I = 1.0 M (NaClO(4))). The activation parameters were found to be DeltaH() = 53.0 +/- 0.6 kJ mol(-1), DeltaS() = -127 +/- 3 J mol(-1) K(-1) and DeltaV(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 38 publications
3
37
2
Order By: Relevance
“…In this work, the fascinating influence of a single cobalt-carbon bond in tuning the reactivity of the Co() center was clearly demonstrated. [25][26][27][28][29] We found that the reaction of XCbl with CN Ϫ , where X = NCCH 2 , CF 3 and CN Ϫ , proceeded via the formation of an intermediate X(CN)Cbl, which subsequently reacts, in the presence of CN Ϫ , to give (CN) 2 Cbl Ϫ . 26 We also found that the mechanism of substituting the axial DMBz trans to the X group in a series of XCbl by CN Ϫ occurred via a dissociative mechanism.…”
Section: Introductionmentioning
confidence: 90%
“…In this work, the fascinating influence of a single cobalt-carbon bond in tuning the reactivity of the Co() center was clearly demonstrated. [25][26][27][28][29] We found that the reaction of XCbl with CN Ϫ , where X = NCCH 2 , CF 3 and CN Ϫ , proceeded via the formation of an intermediate X(CN)Cbl, which subsequently reacts, in the presence of CN Ϫ , to give (CN) 2 Cbl Ϫ . 26 We also found that the mechanism of substituting the axial DMBz trans to the X group in a series of XCbl by CN Ϫ occurred via a dissociative mechanism.…”
Section: Introductionmentioning
confidence: 90%
“…Application of high pressure techniques have been successfully applied to the chemistry of vitamin B 12 and its derivatives. [18][19][20][21][22] Recently some of us studied the reaction of a series of alkylcobalamins (RCbls) with cyanide and found that the kinetic trans effect increases in the order CN Ϫ < CF 3 < NCCH 2 < CF 2 H < CF 3 CH 2 < Me < n-Pr. The mechanism of the reaction of RCbls with cyanide was found to be limiting dissociative (D) in the case of R = NCCH 2 , CF 3 , CN Ϫ .…”
Section: Introductionmentioning
confidence: 99%
“…[22Ϫ36] In the case of the coenzyme, however, evidence for an associative substitution mode was reported. [37] In order to gain further insight into the reasons for this unexpected mechanistic changeover, we have now investigated substitution reactions of trans-[Co(en) 2 (Me)H 2 O] 2ϩ and trans-[Co(en) 2 (Me)NH 3 ] 2ϩ to study the effect of the leaving group on the axial ligand substitution mechanism of these model complexes that include a cobaltϪcarbon σ-bond. These complexes allow us to mimic the active site of the coenzyme since the ammine ligand trans to the CoϪMe bond represents the dimethylbenzimidazole moiety in the coenzyme.…”
Section: Introductionmentioning
confidence: 99%